Mechanical Characteristics of Glass Fibre Vessels - Ali Azhar; Triwilaswandio Wuruk Pribadi; Akhmad Basuki Widodo; Nur Yanu Nugroho (Department of Marine Engineering, Institut Teknologi Sepuluh Nopember, 2025)
Glass fibre vessels in Indonesia, which has thousands of islands, are increasingly used due to their relative low price, light weight, corrosion resistance, and low maintenance costs. However, the aggressive marine environment such as exposure to salt water, ultra violet light, temperature changes, and repeated mechanical loads, affect the service life of this material. Determining the mechanical characteristics of glass fibre vessels is important to prevent structural damage that compromises safety and operations. The purpose of this research is to identify and analyse the condition of shipyards, fibreglass vessels that have been in operation, and examine the mechanical characteristics of glass fibre vessels. The research methods used are literature studies and field surveys to shipyards, glass fibre ships, and testing mechanical characteristics with tensile tests and bending tests. The results obtained from this study are the identification of the condition of the glass fibre shipyard, the condition of the operating glass fibre ship, and the mechanical characteristics of glass fibre ships mostly do not meet the standards of the Indonesian Classification Bureau. Recommendations to improve the quality of production are the location, method, labour, design and materials such as ship resin and laminate layers used during the production process have met and obtained certification set by the Indonesian Classification Bureau.